Systemic melatonin application increases bone formation in mandibular distraction osteogenesis - Izzet ACIKAN; GUL Mehmet; Gokhan ARTAS; Ferhan YAMAN; Gulnihal DENIZ; Ozgur BULMUS; Mustafa KOM; Mustafa KIRTAY; Serkan DUNDAR (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract This study aimed to investigate the effects of different doses of systemic melatonin application on new bone formation during mandibular distraction osteogenesis (DO) in rats. Mandibular DO was performed on 30 adult female Sprague-Dawley rats, which were randomly divided into three groups: control group (CNT), melatonin dose 1 (MLT-D1), and melatonin dose 2 (MLT-D2). A five-day latent waiting period and a ten-day distraction phase followed the surgery. After the surgery, rats from the MLT-D1 and MLT-D2 groups received 25 and 50 mg/kg melatonin, respectively, at 7, 14, 21, 28, and 35 days. The animals were euthanised 28 days after distraction, i.e. at 43 days after surgery. Histological and histomorphometric analyses revealed that the distracted bone area was completely filled with new bone formation in all three groups. The MLT-D2 group exhibited the most new bone formation, followed by MLT-D1 and CNT. The melatonin groups had more osteoclasts than the CNT (p < 0.05). The number of osteoblasts was higher in the melatonin groups than in the CNT group, and the MLT-D2 had more osteoclasts than the MLT-D1 group (p < 0.05). Finally, the osteopontin (OPN) and vascular endothelial growth factor (VEGF) levels were higher in the melatonin groups than in the CNT group, and the MLT-D2 had higher OPN and VEGF levels than the MLT-D1 (p < 0.05). This study suggests that systemic melatonin application could increase new bone formation in DO.